Selective Translation of the Measles Virus Nucleocapsid mRNA by La Protein - Inoue, Yoshihisa; Sato, Hiroki; Fujita, Kentaro; Tsukiyama-Kohara, Kyoko; Yoneda, Misako; Kai, Chieko (Frontiers in Microbiology, 2011)
Measles, caused by measles virus (MeV) infection, is the leading cause of death in children because of secondary infections attributable to MeV-induced immune suppression. Recently, we have shown that wild-type MeVs induce the suppression of protein synthesis in host cells (referred to as "shutoff") and that viral mRNAs are preferentially translated under shutoff conditions in infected cells. To determine the mechanism behind the preferential translation of viral mRNA, we focused on the 5 untranslated region (UTR) of nucleocapsid (N) mRNA. The La/SSB autoantigen (La) was found to specifically bind to an N-5UTR probe. Recombinant La enhanced the translation of luciferase mRNA containing the N-5UTR (N-fLuc), and RNA interference of La suppressed N-fLuc translation. Furthermore, recombinant MeV lacking the La-binding motif in the N-5UTR displayed delayed viral protein synthesis and growth kinetics at an early phase of infection. These results suggest that La induced predominant translation of N mRNA via binding to its 5UTR under shutoff conditions. This is the first report on a cellular factor that specifically regulates paramyxovirus mRNA translation.